The scientificity of quantitative, qualitative and emerging methodologies - Castañeda Mota, María Marcela (2022)
Introduction: It considers the applicability of the scientific mode of knowledge for the resolution of concrete problems of everyday life, individual or collective. Background: From the framework of criteria for scientificity, it is proposed to base the traditional methodological emphasis, with theoretical elements and epistemic and logical supports, to justify the empirical applicability oriented to social welfare. Discussion: Elements of contraposition and overcoming are considered that derive in proposals with theoretical foundation to fulfill objectives covered in the applicability of disciplinary principles; and with this, to frame traditional or emergent methodologies.